2016
DOI: 10.1371/journal.pone.0155529
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Methicillin Resistant Staphylococcus aureus Strains Isolated from Intensive Care Units in Iran: ST22-SCCmec IV/t790 Emerges as the Major Clone

Abstract: IntroductionThe emergence of methicillin-resistant Staphylococcus aureus (MRSA) in different patient populations is a major public health concern. This study determined the prevalence and distribution of circulating molecular types of MRSA in hospitalized patients in ICU of hospitals in Tehran.Materials and MethodsA total of 70 MRSA isolates were collected from patients in eight hospitals. Antimicrobial resistance patterns were determined using the disk diffusion method. The presence of toxin encoding genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
98
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 43 publications
36
98
7
Order By: Relevance
“…The high frequency of MRSA isolates in the present study was in agreement with the findings of the studies in Iran (1), Bolivia (18), and India (19) and is higher than Hungary (20) and Croatia (21). The results of the susceptibility testing showed that all the isolates were susceptible to vancomycin, linezolid, and teicoplanin which is consistent with a previous study in Iran (1) and other studies (16)(17)(18)(19)(20)(21). Although aminoglycosides play an important role in the therapy of serious staphylococcal infections, there have, recently, been reports of increased resistance to this drug worldwide.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The high frequency of MRSA isolates in the present study was in agreement with the findings of the studies in Iran (1), Bolivia (18), and India (19) and is higher than Hungary (20) and Croatia (21). The results of the susceptibility testing showed that all the isolates were susceptible to vancomycin, linezolid, and teicoplanin which is consistent with a previous study in Iran (1) and other studies (16)(17)(18)(19)(20)(21). Although aminoglycosides play an important role in the therapy of serious staphylococcal infections, there have, recently, been reports of increased resistance to this drug worldwide.…”
Section: Discussionsupporting
confidence: 93%
“…According to the literature, there is heterogeneity in the prevalence of MRSA in different regions and countries (1,16). In this study, methicillin resistance was detected in 90.5% S. aureus isolates.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations